PENINGKATAN KAPASITAS PRODUKSI DAN KUALITAS PRODUK KERAJINAN DARI LIMBAH TEMPURUNG KELAPA DI KABUPATEN BANYUMAS - Jati, Eling Purwanto (Faculty of Economics and Business Universitas Jenderal Soedirman, 2014)
The specific objective of this IbM program is improving production capacity andproduct quality of handicrafts product from coconut shell waste of Karya Batok SMEand Wana Karya Abadi SME as partner for this program.Activities in this IbM program include: (1) Advance training to enhance theknowledge, skills and creativity ability of partners to be able to make various kinds ofhandicraft products made from waste coconut shell with a unique design and attractiveas well high quality; (2) Introduction and application of technology as productionequipment, consisting of circle machine, planer machine, profile machine, grindingmachine and dynamo; (3) Improvement of business management; (4) Extent handicraftproduct promotion techniques; (5) Making a media campaign to introduce the handicrafts product to potential consumers.There are significant differences of conditions before and after this IbM program.The production equipment becomes more complete. This affects the quantity and qualityof handicraft products produced by partners. Types of products increased to 22 typesand the sales increased to 15-20 million per month.